1999
DOI: 10.1115/1.2883709
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Response of Cylindrical Shells to Internal Shock Loading

Abstract: The internal shock loading of cylindrical shells can be represented as a step load advancing at constant speed. Several analytical models are available to calculate the structural response of shells to this type of loading. These models show that the speed of the shock wave is an important parameter. In fact, for a linear model of a shell of infinite length, the amplitude of the radial deflection becomes unbounded when the speed of the shock wave is equal to a critical velocity. It is evident that simple (stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 8 publications
1
22
1
Order By: Relevance
“…5. The predominance of these two frequencies has also been verified experimentally by Beltman et al [3]. Within the low-frequency vibrations behind the load, the peak hoop and axial strains from the finite element and shell models differ only by 2-3%, which is expected since the wavelength of these is vibrations fairly large compared to the wall thickness.…”
Section: Comparison Of Transient Shell Model With Femsupporting
confidence: 56%
See 2 more Smart Citations
“…5. The predominance of these two frequencies has also been verified experimentally by Beltman et al [3]. Within the low-frequency vibrations behind the load, the peak hoop and axial strains from the finite element and shell models differ only by 2-3%, which is expected since the wavelength of these is vibrations fairly large compared to the wall thickness.…”
Section: Comparison Of Transient Shell Model With Femsupporting
confidence: 56%
“…For practical cases involving detonations or shock waves in metal tubes, the velocities are small enough that the first branch plays the most important role in the response. The dispersion curves can be used to estimate the most prominent wavelengths in the response: these are the intersection points between the load speed and the dispersion curve, which correspond to steady-state solutions to the shell equations [3,11]. As discussed by Tang, these steadystate solutions exhibit a resonance at the critical velocity υ co corresponding to the minimum of the first branch of the dispersion curve [11].…”
Section: Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenging counteractions lead many 2 Advances in Acoustics and Vibration investigators to propose theoretical and experimental solutions. The dynamic behavior of cylindrical shells was studied experimentally by Finlayson [2], Simkins [3,4], Beltman et al [5], Thomas [6], and Baz et al [7], the results indicated that increasing bullet velocity by expanding pressure step causing the axisymmetric radial vibration to be several times higher than that produced by the static application of the same load. So, the traveling velocity of the moving load affects the amplitude of the radial response and critical velocity, above which the shell response becomes unstable.…”
Section: Introductionmentioning
confidence: 99%
“…[1] and [2]. These observations consist primarily of point measurements of strain, which have been extremely useful for quantitative characterization of structural loading as well as point validation of simulations.…”
Section: Introductionmentioning
confidence: 99%